2009
DOI: 10.1371/journal.pone.0007177
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Collagenolytic Enzyme from a Pathogen of the Great Barrier Reef Sponge, Rhopaloeides odorabile

Abstract: BackgroundIn recent years there has been a global increase in reports of disease affecting marine sponges. While disease outbreaks have the potential to seriously impact on the survival of sponge populations, the ecology of the marine environment and the health of associated invertebrates, our understanding of sponge disease is extremely limited.Methodology/Principal FindingsA collagenolytic enzyme suspected to enhance pathogenicity of bacterial strain NW4327 against the sponge Rhopaloeides odorabile was purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…DABOOR et al (2012) found an optimal activity of 35°C using a mixture of haddock, herring, ground fish and flounder; and at the same time a temperature of 30°C was reported by ROY et al (1996) when studied greenshore crab (Carcinus maenas). SOVIK and RUSTAD (2006) verified a decrease in the enzyme activity in temperatures below 35°C in the guts of prey Brosme brosme and Molva molva, while MUKHERJEE et al (2009), studying sponge (Rhopaloeides odorabile), observed an optimal enzyme activity at 30°C. Enzymes with collagenolytic properties from microbial sources are often objects of investigation, having been reported by WU et al (2010b) when they studied bacterial strains of Bacillus pumilus and determined an optimal enzyme activity at 45°C, showing that more than 50% of residual activity was lost after 5 min of incubation at 70°C or 10 min at 60°C.…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymementioning
confidence: 78%
See 1 more Smart Citation
“…DABOOR et al (2012) found an optimal activity of 35°C using a mixture of haddock, herring, ground fish and flounder; and at the same time a temperature of 30°C was reported by ROY et al (1996) when studied greenshore crab (Carcinus maenas). SOVIK and RUSTAD (2006) verified a decrease in the enzyme activity in temperatures below 35°C in the guts of prey Brosme brosme and Molva molva, while MUKHERJEE et al (2009), studying sponge (Rhopaloeides odorabile), observed an optimal enzyme activity at 30°C. Enzymes with collagenolytic properties from microbial sources are often objects of investigation, having been reported by WU et al (2010b) when they studied bacterial strains of Bacillus pumilus and determined an optimal enzyme activity at 45°C, showing that more than 50% of residual activity was lost after 5 min of incubation at 70°C or 10 min at 60°C.…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymementioning
confidence: 78%
“…KRISTJÁMSSON et al (1995), ROY et al (1996) and BAEHAKI et al (2012) found an optimum pH of 7.0 for enzymes from Atlantic cod (G. morhua), greenshore crab (C. maenas) and Bacillus licheniformis, respectively. MUKHERJEE et al (2009) observed that pH 5.0 improved the activity of enzymes from species of sponge (R. odorabile). The stability of pH has also been reported for aquatic species such as fish, crustaceans, and sponges, and optimal values were found oscillating between < 5.0 and > 10.0 (TURKIEWIC et al, 1991;KRISTJÁMSSON et al, 1995;TERUEL and SIMPSON, 1995;MURADO et al, 2009;WU et al, 2010a;WU et al, 2010b;HAYET et al, 2011;SOUCHET and LAPLANTE, 2011;SUPHATHARAPRATEEP et al, 2011;BAEHAKI et al, 2012).…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymementioning
confidence: 98%
“…Of those reports that have studied the microbiology of diseased sponges, only one has managed to identify a primary pathogen as the causative agent (Webster et al ., 2002). This sponge pathogen produces a collagenase enzyme which degrades the sponge skeletal fibres (Mukherjee et al ., 2009), but this appears to be host species‐specific and has not been identified from other diseased sponge species. Identifying the causative agents of disease is problematic in sponges due to the presence of diverse and host species‐specific bacteria, archaea and other eukaryotes such as algae and fungi.…”
Section: Areas Requiring Additional Research Effortmentioning
confidence: 99%
“…The aetiology of sponge diseases is often difficult to identify and only in a few cases have tissue disintegration and sponge disease been attributed to the presence of bacterial pathogens. For example, an alphaproteobacterium (strain NW4327) producing collagenolytic enzyme was identified as the primary causative agent of necrosis in the sponge tissue of Rhopaloeides odorabile (Webster et al , 2002; Mukherjee et al , 2009). Potential spongin‐fibre invading bacterial pathogens have also been found in the sponge Spongia officinalis (Gaino & Pronzato, 1989) and Ianthella basta (Cervino et al , 2006).…”
Section: Resultsmentioning
confidence: 99%